Covid-19: A Precursor for ODeL in Higher Institutions of Learning in Uganda - Nabukeera Madinah; Matovu Musa (Interdisciplinary Journal of Education, 2021)
As the Covid-19 pandemic persisted, the government of Uganda together with Ministry of Education and Sports authorized education institutions especially universities to implement ODeL (Open Distance e-Learning) teaching and learning to enable education continuity and avoid students from lagging behind. The study used secondary sources to suggest preparation measures, identify ODeL challenges and suggested recommendations. The results indicated: a consistent, wholistic university approach; maintenance of learning outcomes; enduring student-centric, regular and clear communication; creation of many training platforms available in all sizes and shapes; avoidance of mistakes; and the situation though not being perfect, but was going on well.